Vulnerabilities in migrant live-in care arrangements for people with dementia: a comparative analysis of experts’ insights from Germany and Israel - Ulitsa, Natalie; Nebowsky, Anna Eva; Ayalon, Liat; Schweda, Mark; von Kutzleben, Milena (Frontiers in Psychiatry, 2025)
BackgroundThe global rise in dementia among older adults has led to an increased reliance on migrant live-in caregivers, particularly in countries like Germany and Israel. This triadic care arrangement, involving persons with dementia, their families, and migrant live-in caregivers, presents unique challenges and vulnerabilities. These vulnerabilities, deeply intertwined with ethical concerns, are shaped by the socio-cultural and legal contexts of each country. This study aims to explore these vulnerabilities through a comparative analysis of expert experiences in Germany and Israel.MethodA qualitative study was conducted using semi-structured interviews with 24 experts—14 from Israel and 10 from Germany—who have extensive experience in dementia care or migrant caregiving. The interviews were analyzed through qualitative content analysis, focusing on six dimensions of vulnerability: physical, psychological, relational/interpersonal, moral, socio-cultural-political-economic, and existential/spiritual.ResultsThe analysis revealed that all parties in the care triad—persons with dementia, migrant live-in caregivers, and family members—experience distinct yet interconnected vulnerabilities. These vulnerabilities are deeply entangled, manifesting in complex, interrelated ways both within each party and between the different parties in this triadic arrangement. The study also highlighted both similarities and differences in expert experiences between Germany and Israel, reflecting the unique socio-cultural and legal contexts of each country.ConclusionsThe study underscores the multifaceted and interdependent nature of vulnerabilities in migrant live-in care arrangements for people with dementia. By comparing expert insights from Israel and Germany, the research highlights the critical role of national policies and cultural contexts in shaping these vulnerabilities, leading to distinct experiences and challenges in each country. Addressing these vulnerabilities is essential for improving the quality of care and the well-being of all parties involved in the triadic care arrangement.